2021
DOI: 10.3389/fevo.2021.723026
|View full text |Cite
|
Sign up to set email alerts
|

‘Taking Fishers’ Knowledge to the Lab’: An Interdisciplinary Approach to Understand Fish Trophic Relationships in the Brazilian Amazon

Abstract: Trophic levels can be applied to describe the ecological role of organisms in food webs and assess changes in ecosystems. Stable isotopes analysis can assist in the understanding of trophic interactions and use of food resources by aquatic organisms. The local ecological knowledge (LEK) of fishers can be an alternative to advance understanding about fish trophic interactions and to construct aquatic food webs, especially in regions lacking research capacity. The objectives of this study are: to calculate the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 122 publications
(173 reference statements)
2
4
0
Order By: Relevance
“…However, despite this limited sample size, the interviewed fishers still recognized and named most fish species in the Negro River and all fish species in the Tapajos River, thus even a few experienced fishers could provide useful and detailed information on fish biodiversity. Furthermore, the rich knowledge of fish names by the interviewed fishers observed in this study reinforces the findings of our previous studies in both rivers, which show the fishers' detailed knowledge of several aspects of fish ecology, including diet and trophic interactions Silvano and Begossi 2016;Pereyra et al 2021), migrations (Nunes et al 2019), and long-term changes on abundance (Hallwass et al 2020b).…”
Section: Discussionsupporting
confidence: 90%
“…However, despite this limited sample size, the interviewed fishers still recognized and named most fish species in the Negro River and all fish species in the Tapajos River, thus even a few experienced fishers could provide useful and detailed information on fish biodiversity. Furthermore, the rich knowledge of fish names by the interviewed fishers observed in this study reinforces the findings of our previous studies in both rivers, which show the fishers' detailed knowledge of several aspects of fish ecology, including diet and trophic interactions Silvano and Begossi 2016;Pereyra et al 2021), migrations (Nunes et al 2019), and long-term changes on abundance (Hallwass et al 2020b).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore , h. malabaricus has been reported as an omnivorous top consumer feeding on insects and fishes (Rosa et al, 2014). Similarly, previous studies showed a consistency of the overall trophic level estimated for several fish species through local knowledge and stable isotopes analysis (Pereyra et al, 2021). In this sense, fishers while manipulate food items may acquire information regarding trophic habits (Ramires et al, 2015).…”
Section: Resultssupporting
confidence: 76%
“…This arrangement should prioritize the active involvement of fishers in various aspects of the process, including data registration, stock assessments (specifically biomass data), and the evaluation of results. By incorporating the expertise and perspectives of fishers, the effectiveness of management strategies could be enhanced (Silvano and Begossi, 2012; Pereyra et al, 2021).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Even studies by fisheries technologists on industrial purse seine fishing gear are scarce and mostly theoretical (Kim and Park, 2009;Zhou et al, 2019), which warrants more cooperative work with fishers for access to at-sea gear trials. These exchanges of knowledge from fishers to scientists and vice versa are also an excellent way of establishing mutual respect, by highlighting the additive value of connecting both kinds of expertise (Mackinson, 2001;Wedemeyer-Strombel et al, 2019;Pereyra et al, 2021).…”
Section: Introductionmentioning
confidence: 99%